Sales Education beyond the classroom: Building participative learning experiences in Sales Management through the CMGS Method (Case Method with Guest Speakers) - José Luis Ruizalba Robledo; Estefanía Almenta López; María Vallespín Arán (OmniaScience, 2014)
The overarching goal of working through the CMGSMethod (Case Method with GuestSpeakers) in Sales Management courses is toprovide Marketing students with practical knowledge about how a sales managercan deal with a wide variety of possible professional scenarios. Even when thecase method itself is an excellent way to equip students for their prospectiveemployment, the potential of this method can be enhanced with innovativepedagogical tools. Firstly, eight sales managers were invited to the SalesManagement Course as guest speakers. Students were required to prepare forthese sessions, gathering information about the speaker's sector andidentifying areas of special interest. Each speaker shared their hands-onexperience and offered an overview of their field in a workshop, whileanswering the students' questions. These sessions increased the interaction ofstudents with sales professionals, who presented their insights into a careerin sales management. The learning experiences built through these workshopswere narrated by the students in the course blog. Secondly, students were askedto present a scientific paper with the aim of bridging the gap between highereducation and cutting-edge research. This article portrays the reasoning behindthe course as well as the different steps followed during the process. Thecourse finished with encouraging results, suggesting the desirability ofincorporating PL (participative learning) experiences into any marketingcourse.